Formulasi Sediaan Lip Gloss Dari Esktrak Etanol Ubi Jalar Ungu (Ipomoea Batatas L) - Novia Agustia; Rosa Mardiana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Indonesia is a country rich in natural plants that can be used as dyes for cosmetics, one of which is purple sweet potato (Ipomoea batatas L.). This purple sweet potato (Ipomoea batatas L.) grows in the tropics and produces 1.9 million tons of productivity per year. Purple sweet potato (Ipomoea batatas L.) is a natural dye and is safer than synthetic dyes. According to (Dian, 2017), purple sweet potato (Ipomoea batatas L.) contains anthocyanin dyes which play a role in inhibiting the activity of the amulase enzyme and can function as antioxidants. Antioxidants have a function to moisturize the lips and remove dead skin cells, besides that antioxidants are also needed by the body to neutralize free radicals. Lip gloss is a type of lip color preparation that contains high oil so that it gives a moisturizing, shiny or gloss impression. This study used purple sweet potato (Ipomoea batatas L) extract as a natural dye. This study aims to formulate purple sweet potato extract in the form of lip gloss and to see how good the stability of lip gloss is. Purple sweet potato (Ipomoea batatas L) extract was prepared by maceration using 96% ethanol solvent to obtain a liquid extract and then concentrated using a vacuum rotary evaporator to obtain a thick extract. The lip gloss formulation consisted of cera alba, liquid paraffin, vaseline album, emulsifying wax, BHT (Butyl Hydroxy Toluene) nipagin, glycerin, oleum ricini and the addition of purple sweet potato extract coloring. Concentrations used in lip gloss are 0% (F0), 20% (F1), and 35% (F2). Evaluation of lip gloss preparations included organoleptic test, homogeneity, smearing power, pH test, preference and irritation test. The results of the evaluation of the preparations showed that the preparations were homogeneous, and met the requirements well. The results of the smear test showed that the concentrations of 0% (F0), 20% (F1), and 35% (F2) were attached. The results of the preference test showed that at a concentration of 35% (F2) the panelists preferred the most. So it can be concluded that the best preparation is found at a concentration of 35% (F2).